The factors affecting tourism mobile apps usage - Ferhat Seker; Gökhan Kadirhan; Ahmet Erdem (Tourism & Management Studies)
The purpose of this study is to determine the key factor affecting the behaviour of using tourism mobile apps. Contrary to previous studies, the present paper highlights the key factor by evaluating the perceived advantages and technological self-efficacy together. So as to evaluate overall measurement quality and test the hypothesized relationships, a two-step approach was applied. In the first step, confirmatory factor analysis (CFA) was employed to test the validity of the measurement scales. Then, the dataset was analysed using the PLS-SEM method to test the proposed hypotheses. Data were collected from 213 adult participants through an online survey. The study revealed that time-saving is a key determinant of tourism mobile apps usage with the highest beta coefficient (0.335, p<0.01). The effects of convenience (0.293) and technological self-efficacy (0.201) were also significant and positive. However, the perceived financial advantage does not have a significant effect on the behaviour of tourism mobile apps usage. Given the growing value and market potential of mobile applications, this research provides crucial empirical evidence for application developers and tourism researchers about the use of mobile applications for the tourism industry.